2011
DOI: 10.1080/14789949.2011.633615
|View full text |Cite
|
Sign up to set email alerts
|

Group climate, personality, and self-reported aggression in incarcerated male youth

Abstract: Group climate, personality, and self-reported aggression in incarcerated male youth van der Helm, G.H.P.; Stams, G.J.J.M.; van Genabeek, M.; van der Laan, P.H. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 54 publications
(36 reference statements)
4
28
0
Order By: Relevance
“…For example, Van der Helm, Klapwijk, Stams, and Van der Laan (2009) and Schubert et al (2012) showed that a positive or 'open' living group climate characterized by warmth and responsiveness from group workers, opportunities for development, and a safe and structured environment, had a positive effect on the treatment of juvenile delinquents. A 'closed' or repressive climate, on the other hand, has been found to be associated with negative developmental outcomes and aggression (Van der Helm, Stams, Van Genabeek, & Van der Laan, 2012). Therapeutic alliance has also been identified in the literature as a predictor of positive treatment outcomes and can be influenced (Harder, Knorth, & Kalverboer, 2012;Hurley, Lambert, Van Ryzin, Sullivan, & Stevens, 2013;Karver, Handelsman, Fields, & Bickman, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Van der Helm, Klapwijk, Stams, and Van der Laan (2009) and Schubert et al (2012) showed that a positive or 'open' living group climate characterized by warmth and responsiveness from group workers, opportunities for development, and a safe and structured environment, had a positive effect on the treatment of juvenile delinquents. A 'closed' or repressive climate, on the other hand, has been found to be associated with negative developmental outcomes and aggression (Van der Helm, Stams, Van Genabeek, & Van der Laan, 2012). Therapeutic alliance has also been identified in the literature as a predictor of positive treatment outcomes and can be influenced (Harder, Knorth, & Kalverboer, 2012;Hurley, Lambert, Van Ryzin, Sullivan, & Stevens, 2013;Karver, Handelsman, Fields, & Bickman, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Based on two earlier described studies in a Dutch youth correctional facility (van der Helm et al, 2012b) and in a German youth prison (Heynen et al, 2016b), we hypothesized to find an association between the number of aggressive incidents and support and possibilities for growth experienced by the adolescents in the forensic treatment unit.…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising when considering how a primary aspect of relational security is ensuring positive, supportive relationships between patients and staff (Department of Health, 2010), and creation of a positive ward culture (DoH, 2010;Tighe & Gudjonsson, 2012). Supportive relationships between residents and staff are associated with fewer incidents (Chaplin, McGeorge & Lelliott, 2006;Gadon, Johnstone & Cooke, 2006;van der Helm et al, 2012), with perceptions of unfair treatment linked to higher levels of indiscipline in settings such as prisons (Reisig & Mesko, 2009). This has not been examined, however, in high secure psychiatric settings and neither has there been a focus on the full range of potential incidents.…”
Section: Introductionmentioning
confidence: 99%